Project Work Management Addressing the Needs of BVI Learners of EFL - Tatiana S. Makarova; Eugenia E. Matveeva; Maria A. Molchanova; Elena A. Morozova; Natalia V. Burenina (National Research Mordova State University, 2017)
Introduction: it is known that inclusive education that opens access to education and facilitates students with special educational needs to socialize successfully is concentrated in special schools whilst mainstream teachers generally lack the methodology of teaching disabled students inclusively. The aim of the article is searching the best ways of educating students with special needs and providing specific conditions of the educational process in mainstream schools. Materials and Methods: the research is based on the results of fulfillment of a number of projects that deal with teaching and educating blind and visually impaired learners and in which all the authors of the article were involved. The problematic approach, the logical method and observation were applied to the research; analysis, comparison, generalization being the most important components of the study. The quantitative data were collected, analyzed and resumed as well. Results: the impact of project work implementation on academic and social skills development of blind and visually impaired students is shown and various types of projects that can be made by visually impaired learners are presented. The authors give their comments when analyzing different ways of adapting research activities to the needs of BVI learners. When speaking in detail on the role of web tools as maximizers of students' potential the authors refer to their own experience in implementing web tools in project work with blind and visually impaired learners. Discussion and Conclusions: university teacher-training programs should be revised and improved by offering additional courses aimed at educating impaired students through doing research or project work. Special attention should be paid to developing the instructors' project management skills in terms of teaching English as a foreign language to learners with special needs. It should be noted that different methods and various technological tools are to be used in order to develop research and creative skills of blind and visually impaired learners in an EFL classroom. The article itself, its references and links can be used within the course of lectures and seminars on Methodology of Teaching Foreign Languages, and can also be applied when developing a course of re-training of in-service teachers with particular focus on teaching foreign languages to students (pupils) with special educational needs.